Hubungan Dukungan Sosial Keluarga dengan Derajat Hipertensi pada Lansia di Dusun Melase - Bahtiar, Heri; Ariyanti, Maelina; Supinganto, Agus (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
Hypertension is a big and serious problem worldwide. The incidence ofhypertension is more and is often experienced by elderly. One factorsthat cause hypertension is a poor diet such as consuming foods high insodium and fat. So that elderly who have health problems really needfamily support. Data on hypertension sufferers in elderly in Melasevillage are 30 people with an average blood pressure of around 140/90mmHg to 190/110 mmHg which shows that the degree of hypertensionis very high. The purpose of this study was to determine the relationshipbetween family support and the degree of hypertension. This researchmethod is analytic observational with cross sectional approach. Thepopulation study was 30 elderly people using total sampling technique.The data collection method used a questionnaire on each variable.Statistical test used Spearman Rho. The results showed that there were15 people (50%) of sufficient family support, 15 people (50%) of degreeof hypertension stage I category. There is a relationship between familysupport (p = 0.000 <0.05) to degree of hypertension. The conclusion isthe better family support, the lower the degree of hypertension.Suggestions if you want a normal hypertension degree, it must besupported by a good family so that blood pressure can become morenormal.